1988
DOI: 10.1002/ccd.1810150108
|View full text |Cite
|
Sign up to set email alerts
|

Cortical blindness after left internal mammary artery to left anterior descending coronary artery graft angiograph

Abstract: We describe a case of transient cortical blindness following internal mammary artery to left anterior descending coronary artery graft angiography. This dramatic, infrequent, and self-limiting complication so far has not been described in the cardiovascular literature. In the present era of internal mammary artery use for the left coronary artery grafting, the angiographer should be familiar with the diagnosis, prevention, and management of complications previously seen mostly during the posterior cerebral cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
39
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 18 publications
1
39
0
Order By: Relevance
“…The British Cardiac Society has reported an incidence of 0.06% [1] and the National Institutes of Health in the United States of America that of 0.03% [2]. These are thus rare complications, considering the widespread, frequent, performance of coronary angiography.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The British Cardiac Society has reported an incidence of 0.06% [1] and the National Institutes of Health in the United States of America that of 0.03% [2]. These are thus rare complications, considering the widespread, frequent, performance of coronary angiography.…”
Section: Introductionmentioning
confidence: 99%
“…Cortical blindness is better recognized as a complication of cerebral and in particular vertebral angiography having an incidence thereafter of 0.3-2.6% [2] but has also already been described after coronary angiography. Fischer-Williams et al reported one case in 12,367 coronary angiographies, an incidence of 0.008% [3] and Kinn et al reported three cases in over 6,000 such procedures, an incidence of 0.05% [4].…”
Section: Introductionmentioning
confidence: 99%
“…In 3 cases [5], reexposure did not lead to recurrence of CB. In contrast, 1 patient [4] developed CB again. Thus, patients with CB following previous contrast medium exposure may be at increased risk of developing CB at re-exposure.…”
mentioning
confidence: 99%
“…CB after coronary angiography was reported following both high-osmolality ionic [1,2] and modern low-osmolality non-ionic contrast agents [3][4][5][6][7]. The incidence and duration of blindness seem to be unrelated to the dose of contrast medium applied.…”
mentioning
confidence: 99%
See 1 more Smart Citation